Nieruchomości w ofercie private banking - Dziawgo, Leszek (Real Estates in Private Banking, 2006)
Banking in general is more often associated with financial operations than with operations on a real estate market. It is certainly possible to indicate numerous connections between banking and real estate market, and one of the simplest examples are offers of mortgage loans of universal and retail banking or mortgage banking itself. However, in the case of one of the banking segments - private banking, the character of relations between banking and real estate market is different. The real estates are here considered as a very significant subject of investment in the bank's customers assets portfolios. Whereas, asset management is widely understood as management of securities portfolio but also other financial and non-financial assets as well, such as real estate and art. Private banking customers can invest on a real estate market directly and indirectly taking advantage of bank offer and specialized advisory service. What is important here is that the bank offer is not limited to the phase of investing capital on the real estate market.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1109, s. 204-210